Students' Perception and Satisfaction toward EELP - Fahma Liddini Hanifah; Irwan Sulistyanto; M. Syaichul Muchyidin (South Sulawesi Education Development (SSED), 2025)
The role of English in higher education is increasingly critical, particularly in non-English-speaking countries like Indonesia, where students often enter universities with varying levels of English proficiency. Addressing this challenge, the Extended English Language Program (EELP) at Universitas Islam Kadiri Kediri aims to support students in developing foundational English skills essential for academic and professional success. This study examines students' perceptions of the teaching methods, learning materials, and support services provided by EELP, as well as their overall satisfaction with the program. Using a quantitative descriptive design, data were collected through a structured questionnaire with Likert-scale items, and responses from 30 first-semester students were analyzed using descriptive statistics to identify trends in perceptions and satisfaction. The results indicate that most students positively perceived EELP, highlighting interactive teaching methods, effective instructional delivery, and opportunities for practice and engagement as key strengths. Improved English grammar understanding and increased confidence in speaking were among the reported outcomes. However, 13% of students expressed mild dissatisfaction with certain teaching methods, suggesting areas for refinement to better accommodate diverse learning preferences. Overall, the findings underscore the program's success in enhancing students’ foundational English skills while identifying opportunities for improvement. These insights contribute to the theoretical and practical understanding of language education, emphasizing the importance of tailored and interactive approaches to bridging proficiency gaps in higher education.